2016
DOI: 10.1128/genomea.00032-16
|View full text |Cite
|
Sign up to set email alerts
|

First Complete Genome Sequence of Zika Virus ( Flaviviridae , Flavivirus ) from an Autochthonous Transmission in Brazil

Abstract: We report here the genome sequence of Zika virus, strain ZikaSPH2015, containing all structural and nonstructural proteins flanked by the 5′ and 3′ untranslated region. It was isolated in São Paulo state, Brazil, in 2015, from a patient who received a blood transfusion from an asymptomatic donor at the time of donation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 5 publications
0
89
0
10
Order By: Relevance
“…These disease signs were associated with ZIKV infection in the brain, neurodegeneration in the cerebellum, and infiltration of brain tissue with CD4 ϩ and CD8 ϩ T cells. One-day-old neonatal outbred Swiss mice inoculated via a subcutaneous or intracranial route with ZIKV strain SPH 2015, a Brazilian clinical isolate (49), also displayed lethargy, ataxia, and paralysis with evidence of ZIKV infection in the brain (47). Thus, ZIKV infection of neonatal mice can be used to define mechanisms of pathogenesis as an alternative to studying immunocompromised adult mice.…”
mentioning
confidence: 99%
“…These disease signs were associated with ZIKV infection in the brain, neurodegeneration in the cerebellum, and infiltration of brain tissue with CD4 ϩ and CD8 ϩ T cells. One-day-old neonatal outbred Swiss mice inoculated via a subcutaneous or intracranial route with ZIKV strain SPH 2015, a Brazilian clinical isolate (49), also displayed lethargy, ataxia, and paralysis with evidence of ZIKV infection in the brain (47). Thus, ZIKV infection of neonatal mice can be used to define mechanisms of pathogenesis as an alternative to studying immunocompromised adult mice.…”
mentioning
confidence: 99%
“…Cellular entrance, connection and fusion is induced by envelope proteins, premature fusion is averted by pre-membrane (prM), and capsid protein combines Zika nucleic acid to structure nucleocapsid. Regulation of viral replication and transcription along with stimulation of host antiviral responses is regulated by non-structural proteins [6]. A previous study based on nucleotide sequences of NS5 gene indicated three lineages of ZIKV: East African (one strain examined), Asian (one strain examined), and West African (three strains examined).…”
Section: Zikv Genomementioning
confidence: 99%
“…From Thailand to French Polynesia in 2013, this virus has spread to countries of South and Central America infecting more than one million people. Mostly infection is transient and mild but it is strongly neurotropic and cause teratogenic outcomes in fetuses [6].…”
Section: Emergence Of Zikv and Epidemic Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Bununla beraber Cunha ve ark. (17) transfüzyon ilişkili ilk ZİKV infeksiyonu olgusunu Brezilya'dan bildirilmiştir.…”
Section: Si̇vri̇si̇nek Dişi Bulaşunclassified